Development of a High‐Pressure Reactor Based on Liquid‐Flow Pressurisation to Facilitate Enzymatic Hydroxylation of Gaseous Alkanes. Issue 19 (20th September 2019) - Ariyasu, Shinya; Kodama, Yusaku; Kasai, Chie; Cong, Zhiqi; Stanfield, Joshua Kyle; Aiba, Yuichiro; Watanabe, Yoshihito; Shoji, Osami
Abstract: The front cover artwork for Issue 19/2019 is provided by Shoji and co‐workers at Nagoya University (Japan). The image shows the concept of their novel high‐pressure reactor which compresses gaseous alkanes by pumping liquid forcibly (the person wearing a T‐shirt) into the reaction vessel without an exit (the trunk), and pressurizes up to 10 MPa. See the Communication itself at https://doi.org/10.1002/cctc.201901323 . Abstract : " This system can also be adapted for various applications " This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research at https://doi.org/10.1002/cctc.201901323 .